Associations of insulin resistance with cognition in individuals without diagnosed diabetes: Results from the Hispanic Community Health Study/Study of Latinos. (April 2019) - Gonzales, Mitzi M.; Durazo-Arvizu, Ramon A.; Sachdeva, Shruti; Unterman, Terry G.; O'Brien, Matthew J.; Gallo, Linda C.; Talavera, Gregory A.; Kaplan, Robert C.; Cai, Jianwen; Schneiderman, Neil; Espinoza Giacinto, Rebeca A.; González, Hector M.; et al.
Highlights: Is insulin resistance associated with cognition in Latinos without diabetes? With advancing age, insulin resistance associated with better processing speed. With advancing age, insulin resistance also associated with more memory problems. Insulin resistance differentially impacts cognition in older Latinos. Abstract: Aims: Insulin resistance (IR) adversely impacts memory and executive functioning in non-Hispanic whites without diabetes. Less is known in Hispanics/Latinos, despite the fact that Hispanics/Latinos have higher rates of insulin resistance than non-Hispanic whites. We investigated the association between IR and cognition and its variation by age. Methods: Data from 5987 participants 45–74 years old without diabetes from the Hispanic Community Health Study/Study of Latinos. IR was considered continuously using homeostasis model assessment for insulin resistance (HOMA-IR) and also dichotomized based on clinically relevant thresholds for hyperinsulinemia (fasting insulin > 84.73 pmol/L or HOMA-IR > 2.6) and sample-based norms (75th percentile of fasting insulin or HOMA-IR). Cognitive testing included the Brief Spanish English Verbal Learning Test (B-SEVLT), Verbal Fluency, and Digit Symbol Substitution. Results: There was 90% overlap in participant categorization comparing clinically relevant and sample-based thresholds. In separate fully-adjusted linear regression models, age modified the association between HOMA-IR and Digit Symbol Substitution (p = 0.02); advancing age combined with higher HOMA-IR levels resulted in higher scores. Age also modified the association between clinically relevant hyperinsulinemia and B-SEVLT recall (p = 0.03); with increasing age came worse performance for individuals with hyperinsulinemia. Conclusion: The relationship of IR with cognition in Hispanics/Latinos without diabetes may reflect an age- and test-dependent state.